DYNAMIC ASSESSMENT OF CLINICAL SIGNS AND LABORATORY PARAMETERS IN CONGENITAL PNEUMONIA AMONG NEWBORN INFANTS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Congenital pneumonia remains a leading cause of morbidity and mortality among newborn infants, necessitating early diagnosis and timely intervention. Accurate assessment of clinical signs combined with laboratory parameters is critical for guiding therapeutic decisions and predicting outcomes. This study aimed to dynamically evaluate the progression of clinical manifestations and laboratory indicators in neonates diagnosed with congenital pneumonia.